ADHD - Treatment Options and Consequences of Neglect - Wojciechowska, Klara; Turek, Monika; Jaroń, Aleksandra; Jastrzębska, Katarzyna; Witkowska, Maria; Skotnicka, Joanna; Błaszczak, Karolina; Borkowski, Adrian; Sawicki, Mateusz (Quality in Sport, 2024)
Purpose of Research: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most frequently diagnosed neurodevelopmental disorders. It is estimated to occur in approximately 5-10% of children and adolescents. This paper aims to highlight the challenges faced by individuals suffering from ADHD, present risk factors, summarize current treatment methods, and outline the consequences of neglecting treatment. Methods: Databases such as PubMed, Medline, and ResearchGate were used. Basic Results: The goal of ADHD treatment is to reduce the severity of symptoms and improve the social, academic, and emotional functioning of children and adolescents. The choice of treatment and the selection of a specific medication depend on the patient's age and coexisting disorders. Conclusions: ADHD often coexists with other mental disorders, complicating diagnosis and treatment. Lack of or ineffective treatment has consequences such as learning difficulties, disruptions in peer and family relationships. It correlates with higher rates of traffic accidents, accidental injuries, earlier onset, and higher rates of substance abuse.